Overweight and Obesity Among Rural Community in Northern Borneo: Prevalence, Body Weight Perception and Its Associated Factors - Tan Jia Yi; Jyrion Jitour; Syed Shajee Husain; M. Yusof Ibrahim; Fredie Robinson; Syed Sharizman Syed Abdul Rahim; Swe; Aliaa Wahidah Ariffin; Mohamad Helmi Mohamed Asli; Nur Najihah Mohd Noor; Nor Faraheeda Mohd Rahmat; Wan Yan Ru; et al. (Penerbit UMS, 2022)
The World Health Organization (WHO) reported that Malaysia has the highest rate of obesity and overweight among Asian countries. There is an increasing trend in obesity from 11.9% (2015) to 14.8% (2019), according to the National Health and Morbidity Survey (NHMS). This study aimed to investigate the prevalence, bodyweight perception, and associated factors of overweight and obesity among rural communities in Northern Borneo. This cross-sectional study was conducted in one village in Northern Borneo. Adults from 18 to 69 years of age (n = 165) were included in the survey, and data were collected by interview or self-administered questionnaires. Measurements of weight and height were done for body-mass-index (BMI) calculation. The prevalence of overweight and obesity in the village was 71.5%. Kappa statistic indicated only a slight agreement between perceived and actual body weight status (k = 0.163, 95% CI = −0.156 to 0.482, p < 0.000). There were higher odds of being overweight and obese among the middle-aged group (35 – 55 years old) than the younger group (<35 years old) (OR = 3.575; 95% CI: 1.667, 7.667; p < 0.05) and among the married adults than the unmarried adults (OR = 2.196; 95% CI: 1.057, 4.565; p < 0.05). Although age and marital status are non-modifiable factors of overweight and obesity, this research indicated poor consistency between perceived and actual body weight with kappa statistics. The large magnitude of body weight misperception might contribute to overweight and obesity in the rural community.